THE EXPERIENCE OF CANADA’S EDUCATIONAL POLICY AND ITS IMPORTANCE FOR EDUCATIONAL REFORM IN UKRAINE - Макух, Ольга Іванівна; Макух-Федоркова, Іванна Іванівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article describes the Canadian education system and federal higher education funding programs. General scientific methods (analysis, synthesis, comparison, generalization, concretization), chronological and causal analysis, method of scientific extrapolation were used in the research. Elements of application of information of the educational process with the purpose of effective development of the sphere of educational services and maintenance of the quality of education are opened. Formation of its high socio-economic standards for the socio-industrial tasks of the country. Educational innovations were supported by the federal and provincial governments, which built cooperation on the part of the public and the country's industrial potential. In the conditions of change of information technologies and development of "economy based on knowledge", conceptual bases of policy in the field of educational change. The Canadian government has made education a priority. The level of education among the population is a key condition for ensuring the competitiveness of the national economy and, consequently, the welfare of the state. The system of higher education in Canada has a long British tradition, the features of which are formed in the provinces of the country. Educational services in universities and colleges depend on the regional economy and private business, which fund a significant part of research projects. As a result, financial funds are being set up in Canada, one of which is the Canadian Innovation Fund, which implements the tasks of the federal government and the provinces. The priority is to help talented young people and involve them in the industrial life of the country. Federal government policy is also aimed at reforming the program of financial accumulation for education in colleges and universities. Canada's educational policy was based on democracy and the national consolidation of its population